Model of elements affecting the embracement of e-commerce in Nigerian banks - Oluwatobi Alfred Ayanleke (Univerzita Pardubice, 2009)
The aim of this study is to know the models of elements affecting the embracement of e-commerce in Nigerian banks. We can look at the models from both the positive and negative perspective. But we will be focusing on the negative models based on Nigeria and there banks not accepting or not fully embracing e-commerce. Analytical hierarchy process methodology was used to decide on which element is more important and which bank is affected more.
Keywords: Positive; Nigérie; E-commerce; banking; Nigerian banks; bankovnictví; banky; Nigeria